Therapeutic Drug Monitoring (TDM) based precise doing of Vancomycin in Intermittent Hemodialysis (IHD) patients - Sana Saeed; Aamna Habib (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find out the precise dosing of vancomycin in intermittent haemodialysis patients to overcome persistent sub-therapeutic levels so that methicillin resistant S. aureus infections can be avoided. Methods: Total 167 patients were subjected to this study, and their serum vancomycin trough profiles were assessed accordingly. The patients were divided according to gender and age subgroups. Three dose levels, such as 1 g, 1.5 g, and 2 g of vancomycin, were administered, and their trough level was monitored. All the data were subjected to one-way ANOVA (analysis of variance) by SPSS analytical software, and Tukey’s test was applied for means significance. Results: It had been revealed that few patients attained trough level with the administration of 1 g (1st dose) of vancomycin. Similarly, the patients who didn’t attain the maximum trough level post 1 mg administration achieved the maximum trough level after 1.5 g (2nd dose) and 2 g (3rd dose) administration of vancomycin, respectively. A non-significant difference was observed among male and female patients attaining the maximum trough level post 1st, 2nd, and 3rd dose levels of vancomycin. Similarly, a non-significant difference was also observed in different age groups of patients attaining the maximum trough level post 1st, 2nd, and 3rd dose levels of vancomycin. These results showed that therapeutic drug monitoring is an effective way for achieving optimum levels to get the desired response. Conclusion: Patients were found to have sub-therapeutic levels of vancomycin. They were required at least three subsequently upgraded doses to attain therapeutic levels to avoid methicillin-resistant S. aureus infections. Keywords: Therapeutic drug monitoring, Vancomycin, Intermittent hemodialysis, sub-therapeutic